Réponses

2014-03-13T18:29:36+01:00
B= (5x - 7)(3x+1)
   = 15x² + 5x - 21x - 7
   = 15x² - 16x - 7

C= (-2x + 4)(8x-3)
  = -16x² + 6x + 32x -12
  = -16x² + 38 x - 12

D= (1+2x)(3x-9)
  =  3x - 9 + 6x² - 18x
  = -6x² - 15x -9
Meilleure réponse !
  • Utilisateur Brainly
2014-03-13T18:31:25+01:00
On développe les expressions:

B= (5x-7) (3x+1)
B= 15x² +5x -21x -7
B= 15x² - 16x -7

C= (-2x+4) (8x-3)
C= -16x² +6x +32x -12
C= -16x² +38x -12

D= (1+2x) (3x-9)
D= 3x -9 +6x² -18x
D= 6x² -15x -9

Voilà ! J'espère t'avoir aidée ! :)